Identifikasi Faktor Penting Kesiapan Developer dalam Pengimplementasian Konsep Hijau pada Perumahan Terjangkau - Pramudito Muhammad Reza Roosdiawan; Farida Rachmawati (SENTRI: Jurnal Riset Ilmiah, 2026)
The increasing demand for affordable housing in Indonesia necessitates residential developments that balance large-scale quantity with environmental sustainability through green housing concepts. While developers are the primary drivers of green adoption, they face significant organizational challenges. This study aims to identify the critical developer readiness factors essential for the successful implementation of green concepts in the affordable housing sector. A quantitative approach was employed, utilizing a literature review to identify 25 readiness variables, followed by Importance–Performance Analysis (IPA) and Inter-Rater Agreement (IRA) to analyze survey data from subsidized housing developers in East Java. The results highlight that three factors are perceived as the most critical for success, each achieving the highest importance mean of 4.556: Decision-Making Processes, Adequate Financial Budgeting, and Awareness of Green Design Concepts for Housing Provision. These factors emphasize the necessity of integrating sustainability criteria into core procurement procedures and ensuring dedicated funding for green premiums. Furthermore, the study identified five high-priority areas where actual readiness significantly lags behind importance, including collaboration networks and practical knowledge. Identifying these primary factors is crucial as it provides a strategic roadmap for developers and regulators to focus resources on the most impactful organizational capabilities. Enhancing these core readiness factors is essential to bridge the gap between national sustainability targets and actual field implementation.